Benefits of portfolio management systems - Hafþór Þórarinsson 1970- (2020)
In modern today’s world and in last decades, the world of business is getting smaller and companies are moving faster. The company’s area of work is worldwide in many cases, due to globalization, new technology and fast transportations. In this paper the objective is to analyze how PPM is handled at present time in a few companies in Iceland. How they are managing their project portfolio and what they are using to do so. If they are using some systems or tools, what kind of procedures and what is in their opinion are benefits of good, reliable Project Portfolio Management System. As it turns out PPM seems to have still a long way to go and is in some cases in infancy stage in half of the researched companies most have no specific system to manage their portfolio and most regard the Project Portfolio as some kind of Project registry. Still there is a lot of interest to do better and gradually organizations will move towards proper PPM using computer systems to handle the input needed to manage a good Project Portfolio. And with that to benefit from the advantages that comes with it for executing corporation strategy and projects in most efficient way possible.